2001
DOI: 10.4049/jimmunol.166.10.6236
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Fc Receptor-Mediated Antibody-Dependent Phagocytosis in the Host Resistance to Blood-Stage Plasmodium berghei XAT Infection

Abstract: Plasmodium berghei XAT is an irradiation-induced attenuated variant derived from the lethal strain P. berghei NK65, and its blood-stage parasites are spontaneously cleared in immune competent mice. In the present study, we studied the mechanism of host resistance to blood-stage malaria infection using P. berghei XAT. Infection enhanced Ab-dependent phagocytosis of PRBC by splenic macrophages in wild-type C57BL/6 mice. In contrast, FcR γ-chain knockout (FcRγ−/−) mice, which lack the ability to mediate Ab-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 35 publications
2
48
2
1
Order By: Relevance
“…The in vitro inhibitory assay measures the functional activity of antibodies independent of complement or other cellular mediators, and our results suggest they are important in this model system. Evidence has been accumulating to suggest that antibody action via the Fc interaction with monocytes/macrophages plays an important role in protective immunity (2,26,31,40). Such a mechanism is compatible with the results we have obtained in this experiment, and the anti-MSP1 19 antibodies we induced may act in vivo by cooperating with monocytes and/or macrophages.…”
Section: Discussionsupporting
confidence: 81%
“…The in vitro inhibitory assay measures the functional activity of antibodies independent of complement or other cellular mediators, and our results suggest they are important in this model system. Evidence has been accumulating to suggest that antibody action via the Fc interaction with monocytes/macrophages plays an important role in protective immunity (2,26,31,40). Such a mechanism is compatible with the results we have obtained in this experiment, and the anti-MSP1 19 antibodies we induced may act in vivo by cooperating with monocytes and/or macrophages.…”
Section: Discussionsupporting
confidence: 81%
“…For measurement of IFN-␥ production, purified naive CD8 ϩ T cells (2 ϫ 10 5 cells/200 l) were stimulated with plate-coated anti-CD3 (6 g/ml) in the absence of rIL-27 and/or rIL-12 and anti-IL-2 (100 g/ml) for 72 h, and culture supernatants were collected and assayed for IFN-␥ production by ELISA, as described (20). For measurement of proliferation, purified naive CD8 ϩ T cells (2 ϫ 10 5 cells/200 l) were stimulated with plate-coated anti-CD3 (6 g/ml) in the presence of rIL-27 and/or rIL-12 and anti-IL-2 (100 g/ml) for 72 h and pulsed with [ 3 H]thymidine for last 24 h.…”
Section: Ifn-␥ Production and Proliferation Assaysmentioning
confidence: 99%
“…These defense mechanisms largely depend on early innate responses and antigen-specific T helper (Th) cell activation. The importance of the Th1 cytokine gamma interferon (IFN-␥) for protection against malaria has been shown in murine models of malaria (1,11,47,50,54,55,57), with vaccinated animals lacking IFN-␥ showing greatly increased susceptibility, increased parasitemia, and a shorter life span.The role of nitric oxide (NO) in the defense against malaria infection seems to be dependent on the stage of the malaria parasite. In a blood-stage infection with Plasmodium berghei, it was shown that neither NO nor NK cells were important for the control of parasitemia (12, 55).…”
mentioning
confidence: 99%